Porous 3D graphene/multi-walled carbon nanotubes electrodes with improved mass transport and kinetics towards VO2+/VO2+ redox couple. (20th July 2021) - AlNahyan, Maryam; Mustafa, Ibrahim; Alghaferi, Amal; Almarzooqi, Faisal
Abstract: Conventionally, production of 3D graphene (3DG) results in non-uniform particle size and random structures. Although important, the effect of the 3DG particle size on the kinetics of CNT electrodes toward the Vanadium Redox Flow Battery (VRFB) electrolyte has not been investigated. Herein, we manipulate in-lab fabricated CNT sheets with variable particle sizes of electroactive porous 3D graphene (3DG) additives, resulting in variable porous characteristics due to the spacing effect of the 3DG within the as-fabricated CNT fibers. We show that the particle size of 3DG affects both the kinetics and the mass transport capabilities of buckypaper electrodes. The results show that the 3DG additives did not only act as spacers between the CNT fibers opening up channels for increased mass flow to occur, but also improved the heterogeneous rate constants of the reactions. The improvement in kinetics, however, became more significant as the 3DG particle size decreased. Nevertheless, the results also suggest that the use of electroactive materials with controlled particle sizes is a promising strategy for the preparation of porous CNT materials for VRFBs. Graphical abstract Image, graphical abstract